Minimizing Impacts of Future Renewable Energy Development on the World's Desert Ecosystems - McClung, Maureen R.; Moran, Matthew D. (Frontiers in Sustainability, 2022)
Renewable energy development is rapidly increasing across the world, providing affordable and more environmentally sustainable energy to many populations. However, renewable energy, such as solar and wind, can have large land footprints through conversion and modification of natural habitats. One of the more intact habitats on Earth is the desert biome, which contains large areas of roadless regions and, in some places, high biodiversity. Since they are often windy and sunny, desert regions also tend to be rich in renewable energy resources. Using publicly available geospatial data, we calculated that the highest resource areas for wind overlap with 79% of roadless areas and the highest resource areas for solar overlap 28% of roadless areas, globally. High resource wind and solar areas overlap high plant diversity regions by 56% and 79%, respectively, but because high plant diversity desert areas are localized, these overlap areas represent a tiny proportion of the total potentially economically valuable wind and solar regions. These results suggest that desert regions remaining ecologically intact are at risk from renewable energy development. However, strategic siting in abundant, lower quality desert areas might mitigate this issue, especially when areas already impacted by human activity are available. Selected regions presented in detail demonstrate the risks to these habitats and strategies to minimize ecosystem damage. We urge governments and industries to consider placement of wind and solar energy projects that minimize environmental impacts to lands that, up to this point, remain relatively untransformed by human activities.